2015
DOI: 10.1111/asj.12543
|View full text |Cite
|
Sign up to set email alerts
|

The suppressive effect of dietary coenzyme Q10 on mitochondrial reactive oxygen species production and oxidative stress in chickens exposed to heat stress

Abstract: This study was conducted to determine if dietary supplementation with coenzyme Q (CoQ ), which can act as a potent antioxidant and is an obligatory cofactor of mitochondrial uncoupling protein, suppresses the heat stress (HS)-induced overproduction of mitochondrial reactive oxygen species (ROS) and oxidative damage in the skeletal muscle of birds. The carbonyl protein content of skeletal muscle was significantly higher in birds exposed to HS treatment (34°C, 12 h) than in thermoneutral birds (25°C). This incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Reactive oxygen species (ROS) make great contribution to the pathophysiology of PD. Coenzyme Q10 (CoQ10) is an antioxidant that facilitates function of the mitochondrial electron transport chain (Kikusato et al, 2016 ). In vivo and in vitro trials showed that the defect in the activity of mitochondrial complex 1 in PD patients will lead to the disruption of redox equilibrium and neuronal toxicity.…”
Section: Biochemical Biomarkersmentioning
confidence: 99%
“…Reactive oxygen species (ROS) make great contribution to the pathophysiology of PD. Coenzyme Q10 (CoQ10) is an antioxidant that facilitates function of the mitochondrial electron transport chain (Kikusato et al, 2016 ). In vivo and in vitro trials showed that the defect in the activity of mitochondrial complex 1 in PD patients will lead to the disruption of redox equilibrium and neuronal toxicity.…”
Section: Biochemical Biomarkersmentioning
confidence: 99%
“…Increased ROS production has been reported in several HS animals (Huang et al, 2015;Kikusato et al, 2016;Banh et al, 2016). Reduced expression of avUCP in muscule after acute HS exposition of chickens (Kikusato et al, 2016) and heat acclimation of myocytes (Salgado et al, 2017) has been reported. Mujahid et al (2007) observed that 18 h of heat stress (34°C) stimulated the superoxide production in mitochondria, probably by down-regulation of avUCP in muscle tissue.…”
Section: Discussionmentioning
confidence: 96%
“…Hence UCP3 could have an important role under HS conditions, when reduced feed intake and high mitochondrial production of ROS is usually observed (Baumgard and Rhoads, 2013;Slimen et al, 2015). Increased ROS production has been reported in several HS animals (Huang et al, 2015;Kikusato et al, 2016;Banh et al, 2016). Reduced expression of avUCP in muscule after acute HS exposition of chickens (Kikusato et al, 2016) and heat acclimation of myocytes (Salgado et al, 2017) has been reported.…”
Section: Discussionmentioning
confidence: 97%
“…In poultry, heat stress is one of the major factors causing the increased production of mitochondrial reactive oxygen species (ROS) in tissues. Reactive oxygen species accumulating in the cells cause cellular dysfunction by inducing an irreversible damage in molecules such as lipids, proteins, and DNA (Kikusato et al, 2016;Azad et al, 2013). Malondialdehyde is one of the metabolic products of lipid peroxides resulting from lipid peroxidation reaction induced by ROS in tissues (Xiao et al, 2016).…”
Section: Discussionmentioning
confidence: 99%